2021
DOI: 10.1590/fst.23720
|View full text |Cite
|
Sign up to set email alerts
|

Impact of water temperature of chimarrão on phenolic compounds extraction

Abstract: This study evaluated the effect of water temperature (65 °C, 75 °C, 85 °C, 95 °C) on the concentration of caffeic acid, 5-caffeoylquinic acid, 3,4-dicaffeoylquinic acid, 3,5-dicaffeoylquinic acid, 4,5-dicaffeoylquinc acid and rutin in chimarrão aqueous extracts prepared from two commercial types of yerba mate: traditional and coarse ground. The chimarrão preparation simulated the homemade process. Regardless of the temperature, aqueous extracts from the coarse ground had 60% more phenolic compounds than the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Deladino et al (2013) [ 75 ] found a correlation between chlorogenic acid vs. DPPH (R 2 = 0.8429) and gallic acid vs. DPPH (R 2 = 0.9807). Other authors have also confirmed that Yerba Mate has strong antioxidant properties, resulting, among others, from the high content of phenolic components [ 4 , 8 , 9 , 15 , 16 , 17 , 20 , 21 , 22 , 23 , 48 , 77 ].…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Deladino et al (2013) [ 75 ] found a correlation between chlorogenic acid vs. DPPH (R 2 = 0.8429) and gallic acid vs. DPPH (R 2 = 0.9807). Other authors have also confirmed that Yerba Mate has strong antioxidant properties, resulting, among others, from the high content of phenolic components [ 4 , 8 , 9 , 15 , 16 , 17 , 20 , 21 , 22 , 23 , 48 , 77 ].…”
Section: Resultsmentioning
confidence: 81%
“…30% lower at 65 °C, approx. 33% lower at 85 °C, and the lowest at 75 °C [ 22 ]. The authors explained this relationship with probably better solubility of these components in water at high (close to boiling) temperature [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The assays were performed using an extract containing the non-phenolic fraction of açaí added to the standards of phenolic compounds at a concentration of 5 mg L-¹. The purpose of this procedure was to verify that the optimum experimental condition obtained for the separation of the compounds would not be affected by the matrix effect, which could hinder the application of the method in real samples (Silveira et al, 2016). Four repetitions were performed at the central point, totalizing 18 experiments.…”
Section: Multivariate Optimisation and Data Treatmentmentioning
confidence: 99%